The accountability of village funds and to improve the effectiveness of village programs - Arna Suryani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This study aims to analyze the management of village funds and village finances, as well as the inhibiting factors in the management of village funds and village finances. The data was obtained from informants at the research site (Harapan Makmur Village, East Tanjung Jabung Regency, Jambi Province). Data collection is carried out by triangulation in interview observations, literature, and documentation. Data analysis used a qualitative approach based on the NVivo 12 Plus program. The results showed that the management of village funds started early in the planning stage by identifying and selecting programs or activities that were urgent and prioritized for the community. The implementation stage is processed following the Regulation of the Minister of Finance Number 199 of 2017 concerning procedures for allocating village funds and implementing the village income and expenditure budget. Financial recording and reporting have been carried out correctly and adequately, and village funds have also been reported transparently to sub-district and district governments and village communities. Nevertheless, several obstacles are faced by the Harapan Makmur village government in optimizing the management of village funds. These constraints are related to the capacity of village apparatus resources, natural factors, low community support for managing village funds, inappropriate disbursement system, and government policies and regulations that change yearly